2008
DOI: 10.1074/jbc.m802786200
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of HDAC6 for Transforming Growth Factor-β1-induced Epithelial-Mesenchymal Transition

Abstract: The aberrant expression of transforming growth factor (TGF)-␤1 in the tumor microenvironment and fibrotic lesions plays a critical role in tumor progression and tissue fibrosis by inducing epithelial-mesenchymal transition (EMT). EMT promotes tumor cell motility and invasiveness. How EMT affects motility and invasion is not well understood. Here we report that HDAC6 is a novel modulator of TGF-␤1-induced EMT. HDAC6 is a microtubule-associated deacetylase that predominantly deacetylates nonhistone proteins, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
155
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 150 publications
(159 citation statements)
references
References 38 publications
3
155
1
Order By: Relevance
“…Class I HDACs appear to play a key role in repression of the E-cadherin gene promoter as components of a repression complex containing the SMAD3 transcription factor and the Snail and ZEB corepressors (Figure 4). 72 However, RNA interference studies have also suggested that HDAC6, through its ability to deacetylate tubulin and promote SMAD3 nuclear import, is linked to EMT in lung epithelial cells, 73 leaving the roles of specific HDAC isoforms in promoting EMT in question. Future studies using highly selective iso-HDACis as pharmacological tools should be greatly helpful in this regard.…”
Section: Bush and Mckinseymentioning
confidence: 99%
“…Class I HDACs appear to play a key role in repression of the E-cadherin gene promoter as components of a repression complex containing the SMAD3 transcription factor and the Snail and ZEB corepressors (Figure 4). 72 However, RNA interference studies have also suggested that HDAC6, through its ability to deacetylate tubulin and promote SMAD3 nuclear import, is linked to EMT in lung epithelial cells, 73 leaving the roles of specific HDAC isoforms in promoting EMT in question. Future studies using highly selective iso-HDACis as pharmacological tools should be greatly helpful in this regard.…”
Section: Bush and Mckinseymentioning
confidence: 99%
“…Lavage cell pellets were defrosted on ice, and mRNA was extracted as above for C10 cell pellets with the exception that 350 l of RLT lysis buffer was used for total RNA extraction and 250 ng of total RNA was used for first-strand synthesis as described above. The quantity and quality of each individual cDNA sample was validated by qPCR using primers for 36B4 (74) and 18S using the following primer pair (18s-reverse 5=GTCGGGAGTGGGTAATTTGC3=; 18S-forward 5=GAGGGAGCCTGAGAAACGG3=). Transcript expression levels were then determined in Adv-Zta-and Adv-GFP-treated BAL cells by combining equal cDNA amounts and performing real-time quantitative PCR using the mouse Th-17 for autoimmunity and inflammation RT 2 profiler PCR array platform (SA Bioscience).…”
Section: Methodsmentioning
confidence: 99%
“…A549 and HPL1D cells were cultured as previously described (24,25). During treatment with recombinant human TGF-b1 (R&D Systems, Minneapolis, MN), A549 cells were cultured in Dulbecco's modified Eagle's medium plus 0.5% FBS.…”
Section: Cell Culturementioning
confidence: 99%
“…The LMP1 adenovirus (28) was provided by S. Gottschalk (Baylor University School of Medicine, Houston, TX). RT 2 -PCR primers were purchased from Integrated DNA Technologies (36B4, E-Cad, PAI-1, MMP9, vimentin, collagen 1 [25], Fn, alpha smooth muscle actin (aSMA) [29], Snai1, Slug, and ZEB-1 [30]; Coralville, Iowa) or SA Bioscience (Smad 7, SP-C; Frederick, MD).…”
Section: Plasmids and Reagentsmentioning
confidence: 99%